Interconnection structure reinforced nylon composite material and preparation method thereof

By adopting the method of interconnected structure enhancement in nylon 66 composite materials, the cross-linking effect of boric acid and metal salts is used to solve the problem of poor mechanical properties of nylon composite materials in the prior art, and the high tensile properties and tensile resistance of the composite materials are achieved, which is suitable for large-scale production.

CN119859404APending Publication Date: 2025-04-22HENAN INST OF ENG
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510172132.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the prior art, the composite material is prepared by adding boric acid and its salts to nylon through physical mixing, resulting in a smaller improvement in the mechanical properties of the composite material and a lower toughness when the fill amount increases.

Method used

Using the method of interconnected structure enhancement, nylon 66 is dissolved in formic acid solution to form a gel liquid, and then mixed with boric acid and metal salt, and through water replacement and drying, a solid reinforced nylon composite material is formed. This method improves the tensile properties and tensile resistance of composite materials through the cross-linking of boric acid and metal cations.

Benefits of technology

It significantly improves the longitudinal tensile properties and transverse tensile resistance of the composite material, enhances the break strength and elongation of the break of nylon 66, and has a simple preparation process and mild synthesis conditions, which is suitable for large-scale mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859404A_ABST
    Figure CN119859404A_ABST
Patent Text Reader

Abstract

The invention provides an interconnection structure reinforced nylon composite material and a preparation method thereof, belongs to the technical field of reinforced polymers, and aims to solve the technical problem of poor mechanical properties of nylon composite materials. The preparation method of the reinforced nylon composite material comprises the following steps: dissolving nylon into a solvent to prepare a gel solution; mixing the gel solution with boric acid and metal salt to prepare a mixed solution; and replacing the solvent in the mixed solution with water to obtain the solid reinforced nylon composite material. According to the invention, nylon is taken as a matrix, boric acid is taken as a reinforcing phase, metal cations are taken as a bridging agent, and interacts with nylon 66 in multiple forms of hydrogen bonds and coordinate bonds, so that the longitudinal tensile property of the composite material can be improved, and the transverse tensile capacity of the composite material can also be improved. Meanwhile, the preparation process is simple, the synthesis condition is mild, the method is suitable for large-scale batch production, and the industrial application prospect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of reinforced polymers, and in particular relates to a reinforced nylon composite material. Background Art

[0002] As a prominent member of the nylon family, PA66 has the widest application range in the polyamide category. Its outstanding mechanical strength, wear resistance, heat resistance and solvent resistance are its remarkable features. PA66 has obvious application advantages in the fields of automobiles, electronic products, electrical equipment, mechanical parts and transportation equipment. Therefore, how to prepare PA66 hybrid fibers with better performance to expand the application field of PA66 has become the key to current research.

[0003] Common mixing methods in the prior art have been studied more on physical mixing of multiple inorganic substances. Currently developed inorganic substances include materials such as talcum powder, glass fiber, and carbon black. For example, the invention patent application with application publication number CN117165077A discloses a nylon 66 material and a preparation method thereof, which is blended with short glass fiber, nano-scale carbon black powder, and ultrafine calcium carbonate powder, and extruded into a granular final body of nylon 66 material through a twin-screw extruder. Although it improves the mechanical properties of the composite material to a certain extent, the toughness of the mixed material is poor due to physical mixing. The method used adopts physical mixing of multiple substances, without chemical bonding, and the improvement of strength is very limited, and the toughness will be reduced when the filling amount increases to a certain extent.

[0004] Boric acid and its salts have good thermal stability and are not easy to decompose at high temperatures. For example, sodium borate can still maintain a stable crystal structure at high temperatures and can be used in high-temperature ceramics and glass industries. Boric acid is not easily oxidized and has strong reducibility. In the chemical industry, boric acid can be used to produce chemicals such as borides and boric esters. And boric acid is cheap and more suitable for use in industrial production. Boric acid-modified nylon is an engineering plastic with good performance. By adjusting the amount of boric acid added, its mechanical properties and thermal stability can be effectively improved. For example, patent publication number CN107868257A discloses a semi-aromatic nylon-long-chain aliphatic nylon composite and its preparation method, nylon composite material and its preparation method and application, which belong to the field of composite materials. The composite is obtained by mixing semi-aromatic nylon, long-chain aliphatic nylon, boric acid, water and a first antioxidant and then extruding and granulating. Patent publication number CN109021562A discloses a highly efficient flame retardant reinforced nylon composite material and its preparation method, which is made of the following components in mass percentage: nylon 6640-65%; glass fiber 10-35%; brominated polystyrene 10-18%; synergistic flame retardant 1-7%; compatibilizer 2-10%; itaconic acid epoxy 1.5-6%; auxiliary agent 0.5-5%; the synergistic flame retardant is one or two of antimony trioxide and zinc borate. However, in the prior art, boric acid and its salts are added to nylon to prepare composite materials by physical doping, which has little effect on the improvement of the mechanical properties of the composite materials. Summary of the invention

[0005] In view of the technical problem that nylon composite materials have poor mechanical properties, the present invention proposes an interconnected structure reinforced nylon composite material and a preparation method thereof, which has a simpler preparation process, milder synthesis conditions, is suitable for large-scale batch production, and can further improve the tensile properties of the composite material.

[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] A method for preparing an interconnected structure reinforced nylon composite material comprises the following steps:

[0008] (1) dissolving nylon in a solvent to prepare a gel solution;

[0009] (2) mixing the gel solution with boric acid and a metal salt to prepare a mixed solution;

[0010] (3) The solvent in the mixed solution is replaced by water, and a solid reinforced nylon composite material is obtained after drying.

[0011] The nylon is nylon 66.

[0012] The solvent is formic acid.

[0013] The temperature during dissolution in step (1) is 30-50°C, and the mixture is stirred until it is transformed into a gel, preferably for 30-60 minutes.

[0014] The ratio of nylon to solvent is 1g: (3-6)ml.

[0015] In the step (2), the amount of boric acid added is 5-30% of the total mass of nylon and boric acid, and the amount of metal salt added is 5-30% of the total mass of nylon and metal salt.

[0016] During the preparation, the boric acid and the metal salt may be first dispersed and dissolved in a solvent, and then the gel solution in step (1) may be added.

[0017] The metal salts include chlorides, sulfides and nitrates.

[0018] The metal salt is any one of aluminum chloride, magnesium chloride, ferric chloride, ferrous sulfide, copper sulfide, silver nitrate, potassium nitrate or copper nitrate.

[0019] The step of replacing the solvent in the mixed solution with water in step (3) is as follows: adding water to the mixed solution, allowing it to stand, and replacing the water several times until the pH of the mixed solution is not less than 6.

[0020] Furthermore, the solid reinforced nylon composite material obtained in step (3) is placed in a drying oven for drying, cut into powder after drying, dried again, and then hot pressed into sheets. By drying at a specific temperature, the moisture in the composite material can be removed and the structure of the obtained composite material can be optimized. In order to ensure the mechanical properties of the composite material while taking into account the heat treatment efficiency and cost, the drying time is 10 to 18 hours and the temperature is 100 to 120°C.

[0021] The conditions for hot pressing into sheets are: upper mold of vacuum hot press 265-275°C, lower mold 260-280°C, pressure 4-10MPa, heating 3-6min, pressurizing 3-6min, demoulding temperature 60-110°C.

[0022] Beneficial effects of the present invention:

[0023] The preparation method of the present invention uses nylon 66 as a matrix, boric acid as a reinforcing phase, and metal cations as a bridging agent, and a modified nylon 66 composite material is prepared through simple melt blending. In the composite material, boric acid and metal cations act as cross-linking agents, and interact with nylon 66 in various forms of hydrogen bonds and coordination bonds, which can not only improve the longitudinal tensile properties of the composite material, but also improve the transverse tensile resistance of the composite material. In addition, the addition of metal cations can react with amide bonds and hydroxyl groups to form a 3D interconnected laminated structure, further improving the breaking strength and elongation at break of nylon 66. At the same time, the preparation process of the present invention is simple, the synthesis conditions are mild, it is suitable for large-scale batch production, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 XRD pattern of reinforced nylon composite material.

[0026] Figure 2 To strengthen nylon composite materials at 3500-500cm -1 Infrared spectrum of the band.

[0027] Figure 3 For strengthening nylon composite materials at 3400-2800cm -1 Infrared spectrum of the band.

[0028] Figure 4 For PA66 in Comparative Example 1 at 3500-500cm -1 Infrared spectrum of the band.

[0029] Figure 5 The stress-strain curve of reinforced nylon composite material.

[0030] Figure 6 This is the stress-strain curve of PA66 in Comparative Example 1.

[0031] Figure 7 DSC endothermic curves of the materials prepared in Example 2 and Comparative Example 1.

[0032] Figure 8 DSC exotherm curves of the materials prepared in Example 2 and Comparative Example 1. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] A composite material of nylon 66 reinforced with an interconnected structure, the preparation method of which comprises the following steps:

[0036] 1) Weigh 30g of nylon 66, pour in 90ml of formic acid solution, place the formic acid mixture in a water bath, heat and stir at 30°C until it becomes a gel;

[0037] 2) When the solution becomes a gel, add a mixed solution of 1.6 g boric acid, 1.6 g aluminum chloride and 20 ml formic acid, and stir for 30 min to ensure that the boric acid and nylon 66 in the solution are evenly mixed;

[0038] 3) Pour the mixed solution into a culture dish and use pure water as a solvent to replace the formic acid. During this period, change the water every other day for several times. Use pH test paper to measure the pH of the solution to be 6, indicating complete replacement of the formic acid.

[0039] 4) Block nylon 66 / boric acid / M x+ The mixture was placed in a drying oven and dried (120°C, 12h), cut into powder after drying, and dried again at 80°C, and then pressed into sheets using an air hot press. The upper mold of the air hot press was 265°C, the lower mold was 260°C, the pressure was 10MPa, heating was 6min, pressurization was 6min, and the demolding temperature was 60°C. The prepared sample was recorded as 5% nylon 66 / boric acid / MX+.

[0041] Example 2

[0042] A composite material of nylon 66 reinforced with an interconnected structure, the preparation method of which comprises the following steps:

[0043] 1) Weigh 40g of nylon 66, pour in 160ml of formic acid solution, place the formic acid mixture in a water bath, heat and stir at 30°C until it becomes a gel;

[0044] 2) When the solution becomes a gel state, add a mixed solution of 4.4 g of boric acid, 4.4 g of magnesium chloride and 30 ml of formic acid, and stir for 60 minutes to ensure that the boric acid and nylon 66 in the solution are evenly mixed;

[0045] 3) Pour the mixed solution into a culture dish and use pure water as a solvent to replace the formic acid. During this period, change the water every other day for several times. Use pH test paper to measure the pH of the solution to be 6, indicating complete replacement of the formic acid.

[0046] 4) Block nylon 66 / boric acid / M x+ The mixture was placed in a drying oven for drying (120°C, 13h), cut into powder after drying, and dried again at 80°C, and then pressed into sheets using an air hot press. The upper mold of the air hot press was 275°C, the lower mold was 270°C, the pressure was 10MPa, the heating was 5min, the pressurization was 5min, the demoulding temperature was 80°C, and the prepared sample was recorded as 10% nylon 66 / boric acid / M X+ .

[0047] Example 3

[0048] A composite material of nylon 66 reinforced with an interconnected structure, the preparation method of which comprises the following steps:

[0049] 1) Weigh 40g of nylon 66, pour into 240ml of formic acid solution, place the formic acid mixture in a water bath, heat and stir at 30°C until it becomes a gel;

[0050] 2) When the solution becomes a gel state, add a mixed solution of 17.1 g of boric acid and 17.1 g of ferric chloride and 50 ml of formic acid, and stir for 60 minutes to ensure that the boric acid and nylon 66 in the solution are evenly mixed;

[0051] 3) Pour the mixed solution into a culture dish and use pure water as a solvent to replace the formic acid. During this period, change the water every other day for several times. Use pH test paper to measure the pH of the solution to be 7, indicating complete replacement of the formic acid.

[0052] 4) Block nylon 66 / boric acid / M x+ The mixture was placed in a drying oven for drying (120°C, 15h), cut into powder after drying, and dried again at 80°C, and then pressed into sheets using an air hot press. The upper mold of the air hot press was 270°C, the lower mold was 270°C, the pressure was 10MPa, the heating was 5min, the pressurization was 5min, the demoulding temperature was 90°C, and the prepared sample was recorded as 30% nylon 66 / boric acid / M X+ .

[0053] Comparative Example 1

[0054] A nylon 66 composite material, the preparation method comprising the following steps:

[0055] 1) Weigh 30g of nylon 66, pour in 90ml of formic acid solution, place the formic acid mixture in a water bath, heat and stir at 30°C until it becomes a gel;

[0056] 2) Pour the gel solution into a culture dish and use pure water as a solvent to replace the formic acid. During this period, change the water every other day for several times. Use pH test paper to measure the pH of the solution to be 6, indicating complete replacement of the formic acid.

[0057] 3) The block of nylon 66 was placed in a drying oven for drying (120°C, 12h), cut into powder after drying, and dried again at 80°C, and then pressed into sheets using an air hot press. The upper mold of the air hot press was 265°C, the lower mold was 260°C, the pressure was 10MPa, the heating was 6min, the pressurization was 6min, the demolding temperature was 60°C, and the prepared sample was recorded as PA66.

[0058] XRD analysis

[0059] XRD analysis was performed on the composite material of Example 1. The scanning angle was 10 to 80°, and a waveform image was obtained by scanning, such as Figure 1 shown. Figure 1 The XRD spectrum shows that the prepared sample has characteristic peaks of PA66 at 2θ of 20.2° and 24.0°, corresponding to the (001) and (010) crystal planes of PA66, respectively, proving that the synthesized composite sample does not destroy the lattice structure of PA66.

[0060] Fourier transform infrared spectroscopy

[0061] In this experiment, a German Bruker Tebsor-27 Fourier transform infrared spectrometer was used to analyze the surface structure of the composite materials of Examples 1 to 3 and Comparative Example 1. Figures 2 to 4 As shown. Figures 2 to 4 It can be seen that with the increase of boric acid, at 2930cm -1 The wave number and vibration peak of -OH red-shifted, indicating that the boric acid and nylon 66 chains formed an interaction force between the molecules, which also indicates an increase in mechanical strength.

[0062] Tensile properties test

[0063] The method and parameters for the tensile properties test are:

[0064] In order to test the mechanical properties of the prepared splines, the tensile properties of the prepared composite splines and pure splines were tested. The test was carried out using the YG065 electronic universal tensile testing machine designed by Laizhou Electronic Instrument Co., Ltd., China, with a clamping distance of 10mm and a tensile rate of 50mm / min. To ensure the accuracy of the test results, each group of composite fibers was measured five times and the average value was taken to reduce the error.

[0065] The experimental results are as follows Figures 5-6As shown in Table 1, when the boric acid content is too high, the breaking strength and elongation at break are low. The reason may be that too much boric acid causes inorganic accumulation, affecting the mechanical properties. As the boric acid content decreases, the breaking strength and elongation at break reach a peak. However, when the boric acid content is too low, the interaction between boric acid and nylon 66 is weak, so that the increase in breaking strength is not obvious.

[0066]

[0067] Crystallization performance test

[0068] The method and parameters for the crystallization performance test are:

[0069] In order to test the crystallization properties of the prepared strips, melting and crystallization tests were carried out on the prepared composite strips and pure strips. The test conditions were: heating from 25°C to 300°C at a rate of 10°C / min under N2 protection, keeping the temperature for 10 minutes, and then cooling to 25°C at the same rate. All samples were dried in a vacuum oven at 80°C for 8 hours before testing.

[0070] The experimental results are as follows Figures 7-8 As shown in the figure, the melting temperature of PA66 is 260.5℃, the crystallization peak temperature is 233.4℃, and the crystallization starting temperature is 238.4℃; PA66 / BA / M with 10% boric acid x+ The melting temperature is 264.5°C, the crystallization peak temperature is 233.1°C, and the crystallization onset temperature is 238.7°C. It can be seen that nylon 66 / boric acid / M with 10% boric acid and metal cations X+ The melting temperature, crystallization peak temperature and crystallization starting temperature of PA66 are very close to those of PA66 and can be basically ignored. X+ The peak area of ​​the sample is significantly larger than that of PA66, which indicates that the 10% content of boric acid and metal cations in nylon 66 / boric acid / M X+ Has high crystallinity, which is also related to Figure 4 This is consistent with the high breaking strength shown in .

[0071] Example 4

[0072] A composite material of nylon 66 reinforced with an interconnected structure, the preparation method of which comprises the following steps:

[0073] 1) Weigh 40g of nylon 66, pour in 160ml of formic acid solution, place the formic acid mixture in a water bath, heat and stir at 50°C until it becomes a gel;

[0074] 2) When the solution becomes a gel, add a mixed solution of 7 g of boric acid and 4 g of copper sulfide and 50 ml of formic acid, and stir for 60 min to ensure that the boric acid and nylon 66 in the solution are evenly mixed;

[0075] 3) Pour the mixed solution into a culture dish and use pure water as a solvent to replace the formic acid. During this period, change the water every other day for several times. Use pH test paper to measure the pH of the solution to be 7, indicating complete replacement of the formic acid.

[0076] 4) Block nylon 66 / boric acid / M x+ The mixture was dried in a drying oven (120°C, 15 h).

[0077] Example 5

[0078] A composite material of nylon 66 reinforced with an interconnected structure, the preparation method of which comprises the following steps:

[0079] 1) Weigh 10g of nylon 66, pour in 50ml of formic acid solution, place the formic acid mixture in a water bath, heat and stir at 40°C until it becomes a gel;

[0080] 2) When the solution becomes a gel, add a mixed solution of 3 g of boric acid, 2 g of ferrous sulfide and 20 ml of formic acid, and stir for 60 min to ensure that the boric acid and nylon 66 in the solution are evenly mixed;

[0081] 3) Pour the mixed solution into a culture dish and use pure water as a solvent to replace the formic acid. During this period, change the water every other day for several times. Use pH test paper to measure the pH of the solution to be 7, indicating complete replacement of the formic acid.

[0082] 4) Block nylon 66 / boric acid / M x+ The mixture was dried in a drying oven (120°C, 15 h).

[0083] Example 6

[0084] A composite material of nylon 66 reinforced with an interconnected structure, the preparation method of which comprises the following steps:

[0085] 1) Weigh 10g of nylon 66, pour in 40ml of formic acid solution, place the formic acid mixture in a water bath, heat and stir at 30°C until it becomes a gel;

[0086] 2) When the solution becomes a gel state, add 1g of boric acid and a mixed solution of 3g of copper nitrate and 10ml of formic acid, and stir for 60min to ensure that the boric acid and nylon 66 in the solution are evenly mixed;

[0087] 3) Pour the mixed solution into a culture dish and use pure water as a solvent to replace the formic acid. During this period, change the water every other day for several times. Use pH test paper to measure the pH of the solution to be 7, indicating complete replacement of the formic acid.

[0088] 4) Block nylon 66 / boric acid / M x+The mixture was dried in a drying oven (120°C, 15 h).

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an interconnected structure reinforced nylon composite material, characterized in that: The following steps are involved: (1) dissolving nylon in a solvent to prepare a gel solution; (2) mixing the gel solution with boric acid and a metal salt to prepare a mixed solution; (3) The solvent in the mixed solution is replaced by water, and a solid reinforced nylon composite material is obtained after drying.

2. The method for preparing the interconnected structure reinforced nylon composite material according to claim 1, characterized in that: The nylon is nylon 66.

3. The method for preparing the interconnected structure reinforced nylon composite material according to claim 2, characterized in that: The solvent is formic acid.

4. The method for preparing the interconnected structure reinforced nylon composite material according to claim 3, characterized in that: The temperature during dissolution in step (1) is 30-50°C.

5. The method for preparing the interconnected structure reinforced nylon composite material according to any one of claims 1 to 4, characterized in that: The ratio of nylon to solvent is 1g: (3-6)ml.

6. The method for preparing the interconnected structure reinforced nylon composite material according to claim 5, characterized in that: In the step (2), the amount of boric acid added is 5-30% of the total mass of nylon and boric acid, and the amount of metal salt added is 5-30% of the total mass of nylon and metal salt.

7. The method for preparing the interconnected structure reinforced nylon composite material according to claim 6, characterized in that: The metal salts are chlorides, sulfides and nitrates.

8. The method for preparing the interconnected structure reinforced nylon composite material according to claim 7, characterized in that: The metal salt is any one of aluminum chloride, magnesium chloride, ferric chloride, ferrous sulfide, copper sulfide, silver nitrate, potassium nitrate or copper nitrate.

9. The method for preparing the interconnected structure reinforced nylon composite material according to claim 1, characterized in that: The step of replacing the solvent in the mixed solution with water in step (3) is as follows: adding water to the mixed solution, allowing it to stand, and replacing the water several times until the pH of the mixed solution is not less than 6.

10. An interconnected structure reinforced nylon composite material obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Semi-aromatic nylon-long chain fatty nylon compound and preparation method thereof, nylon composite material and preparation method and application thereof

    CN107868257A

  • Efficient and flame-retardant reinforced nylon composite material and preparation method thereof

    CN109021562A

  • Nylon 66 material and preparation method thereof

    CN117165077A